Pengaruh Pajak Daerah Dan Retribusi Daerah Terhadap Kemandirian Daerah Di Kabupaten/Kota Se-Provinsi Jawa Timur Tahun 2018-2023 - Khasanah, Putri Choirul; Susilowati, Lantip (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research examines the influence of regional taxes and regional levies on regional independence in districts/cities throughout East Java Province in 2018-2023. The background to this research is that the implementation of regional autonomy has not been maximized, which is reflected in the low ratio of regional financial independence. Increasing Original Regional Income (PAD), especially from regional taxes and regional levies, is considered a factor that can increase regional independence. This research aims to analyze the influence of regional taxes and regional levies simultaneously or partially on regional independence. Using quantitative methods with an explanatory research approach, this research uses secondary data from the DJPK in the form of the realization of the 2018-2023 APBD. The analysis technique used is panel data regression with E-Views12 software. The research sample consisted of 228 observations using saturation sampling technique. The research results show that simultaneously, regional taxes and regional levies have a significant positive effect on regional independence. Partially, regional taxes have a significant positive effect on regional independence, while regional levies do not have a significant influence.